Justin De Courtenay and the Birth of the Ontario Wine Industry - Jarrell, Richard (Ontario History, 2011)
The introduction of extensive vine growing and commercial wine production to Canada owes its origins to the visionary Justin McCarthy De Courtenay who created the first viable commercial operation in Cooksville in County Peel in the 1860s. He accomplished this through a systematic approach: first, arguing that extensive grape production was possible in the Canadian climate; second, showing that one could produce palatable wine from Canadian-grown grapes; third, engaging government to arouse its interest in a possible new industry; fourth, securing sufficient funds to establish a commercial-scale vineyard and winery; and fifth, through his commercial example, interesting Ontario horticulturists to see the value of vine growing. Despite his departure from Canada in 1869, he had, in less than a decade, established a permanent industry.